(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Transplantation of hematopoietic stem cells from bone marrow or from peripheral or cord blood for cancer, immunodeficiency, or autoimmune disease results in a transient state of complete immunologic incompetence. Immediately after transplantation, both phagocytes and adaptive immune cells (T and B cells) are absent, and the host is extremely susceptible to infection. The reconstitution that follows transplantation has been likened to maturation of the immune system in neonates. The analogy does not entirely predict infections seen in HSCT recipients, however, because the new cells mature in an old host who has several latent infections already.